Achieving highly saturated single-color and high color-rendering-index white light-emitting electrochemical cells by CsPbX3 perovskite color conversion layers. Issue 47 (6th November 2018) - Wang, Cheng-Ming; Su, Yong-Ming; Shih, Ting-An; Chen, Guan-Yu; Chen, Yan-Zhi; Lu, Chin-Wei; Yu, Ing-Song; Yang, Zu-Po; Su, Hai-Ching
Abstract : Saturated emission from light-emitting electrochemical cells integrated with CsPbX3 perovskite color conversion layers. Abstract : Solid-state light-emitting electrochemical cells (LECs) have been thought to be applicable for display and lighting due to their advantages such as simple device architecture, low-voltage operation and compatibility with inert cathode metals. Among the emissive materials of LECs, ionic transition metal complexes (iTMCs) exhibit relatively higher emission efficiency but they show relatively broader emission spectra, resulting in lower color saturation for display application. Here, we demonstrated that by integrating perovskite-based color conversion layers (CCLs) with blue iTMC–LECs, highly saturated green, yellow, red and deep-red and high color-rendering-index (CRI) white LECs can be obtained. The Commission Internationale de l'E'clairage (CIE) 1931 coordinates of the highly saturated single-color LECs are almost on the boundary of the National Television System Committee (NTSC) color gamut, showing their potential application in display. By mixing perovskites of different colors at an appropriate ratio in the CCLs, the white LECs show a CRI >90, which is among the highest reported values, and a correlated color temperature of 2649 K. Hence the proposed technique can also be one of the good candidates for lighting applications. In addition, both the highly saturated single-color and white LECs still exhibit efficient emission for display and lighting applications.